Winds of opportunity: The effects of wind on intertidal flat accretion - Irene Colosimo; Dirk Sebastiaan van Maren; Paul Lodewijk Maria de Vet; Johan Christiaan Winterwerp; Bram Christiaan van Prooijen (Geomorphology, 2023)

The Impact of Wind on Flow and Sediment Transport over Intertidal Flats - Irene Colosimo; Paul L. M. de Vet; Dirk S. van Maren; Ad J. H. M. Reniers; Johan C. Winterwerp; Bram C. van Prooijen (Journal of Marine Science and Engineering, 2020)
Sediment transport over intertidal flats is driven by a combination of waves, tides, and wind-driven flow. In this study we aimed at identifying and quantifying the interactions between these processes. A five week long dataset consisting of flow velocities, waves, water depths, suspended sediment concentrations, and bed level changes was collected at two locations across a tidal flat in the Wadden Sea (The Netherlands). A momentum balance was evaluated, based on field data, for windy and non-windy conditions. The results show that wind speed and direction have large impacts on the net flow, and that even moderate wind can reverse the tidal flow. A simple analytical tide–wind interaction model shows that the wind-induced reversal can be predicted as a function of tidal flow amplitude and wind forcing. Asymmetries in sediment transport are not only related to the tide–wind interaction, but also to the intratidal asymmetries in sediment concentration. These asymmetries are influenced by wind-induced circulation interacting with the large scale topography. An analysis of the shear stresses induced by waves and currents revealed the relative contributions of local processes (resuspension) and large-scale processes (advection) at different tidal flat elevations.